Exploring the Perspectives of South African Parents and Primary Caregivers Living in Low-Income Communities on What Children Need to Thrive within the First 1000 Days of Life - Babatope O. Adebiyi; Tessa Goldschmidt; Fatiema Benjamin; Inge K. Sonn; Nicolette V. Roman (MDPI AG, 2021)
The first 1000 days is recognised as a critical period for the development of children. What children need to thrive in this particular phase of development may be different from any other phase. In South Africa, parents' perception of children's needs within the first 1000 days of life could be considered as emerging. Therefore, this study aims to explore the perspectives of South African parents and primary caregivers on what children need to thrive within the first 1000 days. An exploratory qualitative study design was used to explore the parents' understanding of what children need to thrive in the first 1000 days. A purposive sampling approach was employed to select parents and primary caregivers in low-income communities. In all, thirty respondents participated in the study. The data were analysed using thematic analysis. During the analysis, four themes emerged. The themes included (1) the importance of parenting, care and support; (2) children's need for holistic development; (3) parental roles; and (4) sharing responsibilities. Parents and primary caregivers living in low-income communities understand what children need to thrive within the first thousand days of life. The study could assist policymakers and service providers to design appropriate interventions for parents within these communities.